Impact of the Russia-Ukraine war on Africa: Policy implications for navigating shocks and building resilience - Sherillyn Raga; Heinrich Bohlmann; Alberto Lemma; Dianah Ngui Muchai; Phyllis Papadavid; Dirk Willem te Velde; Chahir Zaki (Overseas Development Institute (ODI), 2024)
This report synthesises the evidence on the impact of the war and its implications on food security in Africa based on country case studies covering Egypt, Ethiopia, Kenya, Morocco, Mozambique, Senegal, South Africa and Sudan, as well as Africa-wide studies utilising econometric modelling techniques. The studies examine the transmission channels of the impact of the Russia-Ukraine war on African economies and their resilience. The report finds that while direct trade exposure is low, Africa relies heavily on Russia and Ukraine for food and fertiliser imports.
Keywords: 330; Economic transformation; Economic growth; Resilience; Women's economic empowerment; Egypt; Ethiopia; Kenya; Morocco; Mozambique; Russian Federation; Senegal; South Africa; Sudan; Ukraine; Africa; Responding to crises